Arsenic in small, mammals - Ismail, A.; Roberts, R.D. (Selper, 1992)
Acute arsenic poisoning had been reported since the nineteenth century from smelting and refining activities. Many of these studies show that arsenic accumulated in the animals is not to concentration greater than 1 ug.g-1. This study shows low levels of arsenic in the tissues of small mammals. For all four species of small mammals analysed; Sorex araneus, Clethrionomys glareolus, Microtus agrestis, and Apodemus sylvaticus showed that arsenic concentr.